ANALISIS STATUS GIZI BAYI PASCA GEMPA BUMI DI KABUPATEN NIAS SELATAN (Jurnal Pangan Gizi dan Kesehatan, 2010)
South Nias District which natural disaster in the year 2005 ago in the form of earthquake at 8.6 Richter scale still including district with severe nutritional status children including baby which still was high. In the year 2005, there was about 11.72% suffer malnutrition baby and even in the year 2007 counted 32% baby of including malnutrition category. This study in May until October 2008, analyzed descriptively with design study was cross sectional. The chosen study location was services-region of the Primary Health Centre (PHC) of Lolomatua, PHC of Amandraya and PHC of Teluk Dalam. Population study was entire family owning baby with amount of sample entirely counted 364 babies. The study instruments (equipments) were using question worksheet, Weight-Baby Instrument, Long-Grader Instrument. Data was processing through editing process, coding, and tabulating. Data analysis done seen number from each every result-studied, was later then was description.The result showed that only 11.5% baby given by colostrums. The nutritional status pursuant to Weight/Age showed that 52.5% including in mild category, 36.5% in normal status, and 6.3% in severe status.